Treatment of Orthopedic Implant Surface with Blood Serum-Based Composition Improves Their Biocompatibility - Lazarenko, G. O.; Lazarenko, O. M.; Guryanov, V. G.; Alekseyeva, T. A.; Furmanov, O. Yu. (Problems of Cryobiology and Cryomedicine, 2018)
Probl Cryobiol Cryomed 2018; 28(1): 034–038